2015
DOI: 10.1177/0148607114567901
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Rehabilitation in the Intensive Care Unit

Abstract: The maintenance of homeostasis after severe injury requires the restoration of the physiological regulation of food intake. A wide array of functional alterations can hinder the intake of adequate amounts of nutrients to support the recovery from critical illness. These alterations encompass changes in the preprandial phase, reflected by a loss of appetite; changes in the prandial phase, yielding swallowing disorders; and changes in the postprandial phase, including impairments of gastric emptying, gut motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 63 publications
(67 reference statements)
0
16
0
5
Order By: Relevance
“…Successful LMV and transition from the ICU to ward marks a significant point in the trajectory of critical illness 28 and the beginning of the journey to recovery. Although no formal guidelines for transitioning patients from EN to an oral diet exist specifically for the recovering critically ill, Massanet et al 29 propose permanent discontinuation of EN only when a patient has demonstrated the ability to consume >75% of daily caloric needs. Half of the patients who transitioned from EN to an oral diet in the first 7 days following LMV, whereby EN was discontinued prior to initiation of any oral diet, did not have the opportunity for assessment of oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Successful LMV and transition from the ICU to ward marks a significant point in the trajectory of critical illness 28 and the beginning of the journey to recovery. Although no formal guidelines for transitioning patients from EN to an oral diet exist specifically for the recovering critically ill, Massanet et al 29 propose permanent discontinuation of EN only when a patient has demonstrated the ability to consume >75% of daily caloric needs. Half of the patients who transitioned from EN to an oral diet in the first 7 days following LMV, whereby EN was discontinued prior to initiation of any oral diet, did not have the opportunity for assessment of oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of obese individuals have reported an inverse correlation between insulin resistance and hyperinsulinemia with ghrelin concentration [3,13]. Increased plasma levels of ghrelin due to fasting have been reported to reduce after eating, especially foods rich in sugar and fat [14].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Oral feeding is a real challenge in ICUs. 12 The barriers to food intakes are numerous 26,27 and related to illness effects (such as anorexia, 28,29 changes in the perception of food taste, 30 and disturbed gastrointestinal function 31 ), eating difficulties, and organizational processes. 32 If regular and disease-specific diets are generally prepared to cover 100% of the daily energy requirements (as demonstrated by the present simulation), they provide on average only 0.8 g/kg/d protein.…”
Section: Discussionmentioning
confidence: 99%